Soil water seasonal and spatial variability in Northeast Brazil - de Oliveira Aparecido, Lucas Eduardo; Lorençone, Pedro Antonio; Lorençone, João Antonio; de Meneses, Kamila Cunha [UNESP]; de Moraes, José Reinaldo da Silva Cabral; de Farias, Maryzélia Furtado (Springer Nature, 2021)
The Brazilian Northeast has great agricultural potential; however, the region suffers from high variability in precipitation. Water is the main element for plant development, and its entry and exit in the soil can be counted by water balance (WB). Therefore, the objective of this study was to determine the spatial and seasonal water conditions in Northeastern Brazil and thus show that the region can be a major agricultural producer. A historical series of rainfall and air temperature from 1950 to 1990, collected from 1536 surface weather stations, representing the entire region, was used. Potential evapotranspiration (PET) was estimated using the Thornthwaite (1948) method and WB by the Thornthwaite and Mather (1955) method, using an available water capacity (WC) of 100 mm, as it is the value used to characterize water availability. Descriptive analysis was performed to identify the variations of the data set, and the probability test was performed by the Kolmogorov–Smirnov method. The data were specialized using the kriging method. The distribution of air temperature values showed that the region had a temperature between 20 and 29 °C. The state of Maranhão (MA) was the warmest, with a probability of occurrence of 28 °C reaching 92%. MA is a state with climatic classes like Am, Aw, and As according to Köppen (1936). The rainfall in the northeast was between 955 mm annual−1 and 1600 mm annual−1, with the highest concentration in the state of MA and the lowest in Rio Grande do Norte (RN). Soil water storage (STO) was greater in January to June, mainly on the coast. Most of the water surplus (EXC) was distributed between May and July, a total of 60%, concentrated in MA and the northeastern coast. The averages were 200 mm annual−1 to 700 mm annual−1 for the water deficit (DEF), with the highest values concentrated in the Ceará (CE) state, with a high probability of occurrence. In CE the classes As and BSh according to Köppen (1936) predominate. The general mean of the region Northeast Brazil for STO, EXC, and DEF was 43.6 (± 17.6) mm, 231.4 (± 276) mm, and 430.6 (± 168.6) mm, respectively.
Keywords: Agricultural planning; Climate modeling; Köppen classification (1936); Potential evapotranspiration; Water storage